2007
DOI: 10.1152/ajpgi.00138.2007
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory role of phosphoinositide 3-kinase in gastric acid secretion

Abstract: The gastric parietal cell is responsible for the secretion of HCl into the lumen of the stomach mainly due to stimulation by histamine via the cAMP pathway. However, the participation of several other receptors and pathways have been discovered to influence both stimulation and inhibition of acid secretion (e.g., cholinergic). Here we examine the role of phosphoinositide 3-kinase (PI3K) in the modulation of acid secretion. Treatment of isolated gastric glands and parietal cells with the PI3K inhibitor, LY29400… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 40 publications
1
34
0
Order By: Relevance
“…For instance, histamine stimulation of gastric parietal cells increases phosphorylation of AKT by ϳ40% and substantially increased acid secretion (55). Similarly, a relatively modest increase in AKT phosphorylation in Caco-2 cells in response to LABEL sulforaphane increases mRNA levels of phase II enzyme transcription 3-6-fold (56).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, histamine stimulation of gastric parietal cells increases phosphorylation of AKT by ϳ40% and substantially increased acid secretion (55). Similarly, a relatively modest increase in AKT phosphorylation in Caco-2 cells in response to LABEL sulforaphane increases mRNA levels of phase II enzyme transcription 3-6-fold (56).…”
Section: Discussionmentioning
confidence: 99%
“…H 2 R stimulation by histamine was shown to potently inhibit phospholipase A2 activity, triggering arachidonic acid synthesis . Interestingly, some actions mediated by H 2 R, such as modulation of cell proliferation and gene expression, are shown to involve the modulation of signaling cascades that are usually associated with tyrosine kinase receptors, such as the extracellular signal-regulated kinase (ERK1/2) or phosphoinositide 3-kinase pathway (Leopoldt et al, 1997;Mettler et al, 2007;Bonini et al, 2011;Luo et al, 2013;Alonso et al, 2016). In addition, histamine or H 2 R agonists inhibit the activity of NADPH oxidase, the enzyme responsible for the generation of reactive oxygen species (ROS), in myeloid cells (Aurelius et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the reported observations, our data raise the possibility that PI3K and TRIM50 may coordinately stimulate tubulovesicular dynamics for acid secretion in parietal cells. However, controversy exists regarding the specific function of PI3K in acid secretion; Lang et al (34) reported that a PI3K inhibitor blunts acid secretion in parietal cells, and Mettler et al (35) observed that the inhibitor adversely facilitates acid secretion. Based on the different effects between the short and long term treatments of PI3K inhibitors in our cDNA expression experiments, it may be important to carefully examine the temporally confined effects of the inhibitors on acid secretion in parietal cells.…”
Section: Discussionmentioning
confidence: 99%